2011
DOI: 10.1007/s11199-011-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

When Male Norms Don’t Fit: Do Traditional Attitudes of Female Colleagues Challenge Men in Non-traditional Occupations?

Abstract: Our study examined whether traditional attitudes of female colleagues toward the male role negatively impact the psychological health of German men in nontraditional occupations and whether these relationships are mediated by social stressors at work. Traditional attitudes are presented as a threefold concept: Attitudes of female colleagues toward male anti-femininity, status, and toughness were measured. One hundred and thirteen men and 174 of their female colleagues from eastern parts of Germany and working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…They stated that they had to take full charge of classes when their mentor teachers were absent, which included performing tasks such as dishing up food for learners during breaks and sweeping floors after they had eaten (most of the schools in the study had soup kitchens). This is in line with the finding of Sobiraj et al (2011) that males in femaledominated professions have to perform stereotypically 'female' tasks in order to gain acceptance.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…They stated that they had to take full charge of classes when their mentor teachers were absent, which included performing tasks such as dishing up food for learners during breaks and sweeping floors after they had eaten (most of the schools in the study had soup kitchens). This is in line with the finding of Sobiraj et al (2011) that males in femaledominated professions have to perform stereotypically 'female' tasks in order to gain acceptance.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Sobiraj, Korek, Weseler and Mohr (2011) report on a study assessing specific attitudes toward the male role, particularly with regard to masculinity. The authors questioned female employees in female-dominated occupations about their attitudes towards men in these roles, including male teachers in German pre-schools, and asked their male colleagues to self-evaluate their psychological health.…”
Section: Introduction: Men As Teachers In the Early Gradesmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies that have examined masculinity ideology in Germany to date (Sobiraj, Korek, Weseler, & Mohr, 2011;Thiele, 2004Thiele, , 2005Thiele et al, 2001;Teuber et al, 2006) have provided evidence of the transferability of the conceptualizations to the German social context. However, more empirical evidence is needed to confirm this.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Sobriaj, Korek, Weseler, & Mohr (2011) discovered that male job satisfaction in nontraditional jobs was inversely related to social stressors such as interpersonal conflicts resulting from female attitudes toward men in nontraditional careers that occur in their work environments. Wharton and Baron (1987) found that men had greater levels of job satisfaction in female-dominated workplaces over mixedgender settings, which they attributed to a man's likelihood to receive better treatment due to the superior social position that is ascribed to their maleness.…”
Section: Nontraditional Careersmentioning
confidence: 99%